Implementation of Green Accounting in Waste Management at The Aqma Cikampek Clinic, Karawang Regency - Ricka Khasanah; Lilis Lasmini; Ade Trisyanto (International Journal of Economics and Management Research, 2025)
Suboptimal medical waste management has a negative impact on the environment and public health. Aqma Clinic Cikampek has implemented a waste management system according to standards, but the recording of environmental costs is still combined with general operational costs without any specific classification, thus hampering transparency and effectiveness of waste cost management. This study uses a descriptive qualitative method with data collection techniques through interviews, observations, and document analysis related to environmental cost recording. The results show that Aqma Clinic still carries out medical waste management according to procedures such as separating infectious and non-infectious waste and collaborating with third parties for waste disposal. However, the recording of waste management costs has not been done separately and still uses the historical cost method. The study recommends the implementation of Green Accounting with the Activity-Based Costing (ABC) method to improve transparency and accountability of environmental costs. This study concludes that the implementation of Green Accounting at Aqma Clinic is still partial and has not been integrated into the formal accounting system. Therefore, it is necessary to develop a more structured and transparent environmental cost recording system to support operational sustainability